Kosmogonia w pigułce, czyli próba analizy 95 strofy Atmopadeśa Śataki Narajany Guru - Urbańska, Hanna (Instytut Studiów Klasycznych, Śródziemnomorskich i Orientalnych Uniwersytetu Wrocławskiego, 2015)
Narayana Guru, one of the Advaita Vedanta contemporary representatives in Kerala. This article is devoted to the concept of cosmogony in the works of Narayana Guru, which were compressed in an intriguing and enigmatic manner in one of the last strophes of this philosopher’s most importanat poem, the Atmopadeśa Śatakam (AŚ 95).
Keywords: filozofia indyjska; Adwajtawedanta; Narajana Guru; Kerala